Antecedents of primary and secondary acute social withdrawal - Frankova, Iryna (Psychosomatic Medicine and General Practice, 2017)
Background. The phenomenon of acute social withdrawal (ASW) is becoming more common and widespread nowadays and can be characterized by complete solitude/alienation from society for 6 months or longer. Previous studies of the ASW included patients with mental disorders and were focused on the psychopathological features of secondary ASW caused by depression, social phobia, or bulimia. Aim. To increase the effectiveness of acute social withdrawal differential diagnostics by determining the etiopathogenetic factors of its development and psychopathological features to improve further management of this condition. Materials and methods. At the Department of Psychosomatic Medicine and Psychotherapy of Bogomolets National Medical University 70 patients with ASW were examined: the first experimental group (EG1) - patients with mental disorders and ASW (n = 42), and the second (EG2) - a mentally healthy contingent with primary ASW (n = 28). Healthy people without ASW (n=56, control group, CG) as well were examined. The following methods were used: Buss Durkee Hostility Inventory, Victim Behavior Questionnaire, Toronto Alexithymia Scale (TAS-26), Leongard-Schmishek Accentuated Personality Trait Questionnaire, Life Event Questionnaire (LEQ), Chaban Quality of Life Scale. Results. Comparing EG and CG regarding significance, there were determined several differences. The level of alexithymia in the EG was significantly higher than in the CG (p<0.005). The quality of life in the EG was significantly lower than in the CG (p<0.005). According to the Leongard-Schmishek test in EG accentuated personality traits such cyclothymia, hyperthymia, dysthymia, anxiety (p<0.005), pedantic (p<0.05), demonstrativeness (p <0.1) were significantly higher than in the CG. According to the Buss-Durkee Hostility Inventory, such indicators as resentment (p<0.005), irritability (p<0.05), suspicion (p<0.05) and, as a consequence, an index of aggression (IA), (p<0.05) were significantly higher than in CG. The results of Life Traumatic Events Questionnaire (LEQ) demonstrated that the impact of traumatic events index (p<0.05) and the trauma index (TI) (p<0.05) in EG were significantly higher than in the CG. As a result of the comparison of the correlation matrices of the E1 and the E2, it was found that the groups differ both in the number of statistically significant links and in the correlation structure. Conclusion. In this study, the psychopathological features of patients with ASW were determined in comparison with healthy control group. It was confirmed that the patients with primary ASW differ from patients with secondary ASW and have other antecedents of this behaviour.